In situ facile bubble-templated fabrication of new-type urchin-like (Li, Mo)-doped Lix(Mo0.3V0.7)2O5 for Zn2+ storage. Issue 34 (17th August 2017) - Qu, Gan; Zhao, Lulu; Jia, Shuangfeng; Zheng, He; Li, Lei; Ma, Wenhao; Yang, Wanjun; Wang, Hai; Tang, Yiwen; Wang, Jianbo
Abstract : The fabricated new-type urchin-like (Li, Mo)-doped Li x (Mo0.3 V0.7 )2 O5 displays a unique electronic structure and superior storage performance for Zn 2+ . Abstract : Interstitial (Li) and substitutional-type (Mo) co-doped new-type urchin-like Li x (Mo0.3 V0.7 )2 O5 (LMVO) is fabricated via in situ gas bubble template strategy, which leads to distinctive conductivity, high number of active sites, reversible ion intercalation and accessible redox couple. Consequently, the electrochemical performance of LMVO is enhanced enormously owing to the hollow morphology and unique electronic structure. The charge storage capability of the synthetic LMVO is investigated in Mg 2+ and Zn 2+ electrolytes as well as Li + electrolyte, due to the similar radius, higher charge, abundant reserve and rational cost. As a result, LMVO achieves a specific capacitance of 484 F g −1 at 1 A g −1 in Zn 2+ electrolyte, which apparently surpasses the performance in Li + and Mg 2+ electrolytes. Moreover, the assembled LMVO//LMVO device delivers a specific capacitance of 117 F g −1 at 0.8 A g −1, which indicates large potential for application.